Incidence of Seroma Formation in Mesh Abdominal Hernioplasties: Irrigated Versus Non-Irrigated Wounds - Hasan, Muhammad Shujah; Ilyas, Sohail; Ashraf, Imran; Laghari, Muhammad Ajmal; Joyia, Ahmed Bilal; Nazir, Fahad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency of seroma formation after abdominoplasty using mesh repair with wound irrigation versus without wound irrigation. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Aug 2023 to Jan 2024. Methodology: This study enrolled 52 patients who underwent mesh repair of ventral hernia of abdomen. After randomization, patients were allocated to one of two groups labelled Irrigation of Wound (WI) Group versus No Irrigation of Wound (NIW) Group. The frequency of formation of seroma was chosen as the primary outcome. Statistical tests were applied for data analysis where a p-value ≤0.05 was considered as significant. Results: On analysis, it was noted that 2(7.7%) patients in WI Group showed signs of seroma formation, and experienced seroma development 7 days after mesh repair of hernia. During the first few days following surgery, none of the patients experienced seroma. In WI Group, 22(92.3%) patients did not experience seroma development. After mesh repair, a total of 9(34.6%) patients in NWI Group developed seroma, of these, 3(11.5%) developed seroma within a week of mesh repair and 6(23.1%) developed seroma after 7 days of surgery. Conclusion: Saline wound irrigation was noted to have lowered the incidence of seroma formation following mesh repair of abdominal hernia.